Renal tumors and second primary pancreatic tumors: a relationship with clinical impact? - Müller, Sascha A.; Pahernik, Sascha; Hinz, Ulf; Martin, David J.; Wente, Moritz N.; Hackert, Thilo; Leowardi-Bauer, Christine; Haferkamp, Axel; Büchler, Markus W.; Schmied, Bruno (Patient safety in surgery, 2012)
The occurrence of synchronous or metachronous renal cell carcinoma and pancreatic tumors has been described only in a few cases in the scientific literature. The study of double primary cancers is important because it might provide understanding of a shared genetic basis of different solid tumors and to detect patients at risk for secondary malignancy.